A cross-sectional study of Iraqi patients investigating HPSE SNPs and the incidence of hepatocellular carcinoma - Suhair Sadai Mahmood; Sabah Ali Jaber Alhelu; Khaleel Ibrahim Ismael; Abbas AbdulWahhab Jumaah; Ban Thabit Saeed; Luai Farhan Zghair; Ali Qais Abdulkafi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
In this study, 30 cases from different hospitals in Iraq were included, and they were divided into two groups (a patients group of 15 cases) (a control group of 15 cases). Patient groups were divided according to gender, 12 males (80%) and three females (20%) in the patient’s group while five females (33.3%) and 10 males (6.6%) in the control group. Information related to patients was collected within the study period of 14 months (July 1, 2019 to September 2, 2020). The demographic data of the patients were analyzed using the statistical analysis program IBM SOFT SPSS 22, where the true value and the arithmetic mean of the results were calculated, and the value of the statistical significance to know the type of relationship was also extracted. The results found rs 12503843 with HCV (CC for eight patients were distributed, six HCV positive and two negative patients; CT for five patients were distributed, four patients HCV positive and one negative patient; TT for two patients were distributed with two positive patients). As for the distribution of patients according to the results of the statistical relationship between rs 12331678 with HCV (six cc patients were distributed as five positive HCV and one negative; CA for six patients distributed as two negative HCV and four positive HCV). Finally, we concluded in this study; it was described that heparanase (HPSE) (rs 12331678 and rs 12503843) with the incidence of hepatocellular carcinoma, and a statistically significant relationship was found with a p-value < 0.01.